Homemade fenestration and chimney techniques for the left subclavian artery revascularization during zone 2 thoracic endovascular aortic repair - Ye, Jiacheng; Li, Yuliang; Lu, Yue; Wang, Yongzheng; Liu, Bin; Chang, Haiyang (Frontiers in Cardiovascular Medicine, 2023)
Background: To investigate the safety and efficacy of homemade fenestration and chimney techniques for the left subclavian artery (LSA) revascularization during zone 2 thoracic endovascular aortic repair (TEVAR). Methods: From February 2017 to February 2021, 41 patients undergoing fenestration technique (group A) and 42 patients undergoing chimney technique (group B) to preserve the LSA during zone 2 TEVAR were enrolled in the present study. The procedure was indicated for dissections with unsuitable proximal landing zone with refractory pain and hypertension, rupture and malperfusion, and high-risk radiographic features. The baseline characteristics, peri-procedure, and follow-up clinical and radiographic data were recorded and analyzed. The primary endpoint was clinical success, and the secondary endpoints were rupture-free survival, LSA patency, and complications. Aortic remodeling, defined as patency, partial and complete thrombosis of the false lumen, was also analyzed. Results: Technical success was achieved in 38 and 41 patients in groups A and B, respectively. Four intervention-related deaths were confirmed, two in each group. Immediate post-procedural endoleaks were detected in two and three patients in group A and B, respectively. No other major complications were found in either group, except for one retrograde type A dissection in group A. During follow-up, the initial clinical success rates were 90.24% and 92.86% in groups A and B, respectively. The primary and secondary mid-term clinical success rates were 87.5% and 90% in group A, and both of them were 92.68% in group B. Rupture-free survival and LSA patency were not significantly different between the two groups. The incidence of complete thrombosis in the aorta distal to the stent graft was 67.65% and 61.11% in groups A and B, respectively. Conclusions: Apart from the lower clinical success rate of fenestration technique, both physician-modified techniques are available for LSA revascularization during zone 2 TEVAR and significantly promote favorable aortic remodeling.